Ipsilateral Pilon and Calcaneus Fractures: Treatment with Circular Frame without Spanning Ankle Joint - Dimitroulias, Apostolos (Strategies Trauma Limb Reconstr, 2019)
This case report describes the treatment of a 48-year-old female patient, smoker, with a closed comminuted pilon fracture (AO/OTA 43-C2.1) and ipsilateral displaced intra-articular calcaneus fracture (AO/OTA 82-C3). Two independent circular frames were applied in a way to preserve tibiotalar range of motion (ROM). The posterior facet of the calcaneus fracture was reduced through a small incision anterior to the tip of the distal fibula. A frame consisting of a two-third ring was applied to the talus and a footplate to the calcaneus was used to hold the reduction of the posterior facet and to correct varus and length. Pilon fracture was similarly reduced with a percutaneous reduction technique and stabilized with the standard two Taylor spatial frame (TSF) rings. During the course of treatment, the tibiotalar joint ROM was maintained. The frame for the calcaneus fracture was removed 10 weeks after the surgery and the frame for the pilon fracture was removed 16 weeks after the surgery. The patient’s last follow-up was 34 months after the injury. She was ambulating independently without limp and she had resumed the preinjury activity level. She had symmetric tibiotalar ROM and 50% reduction in subtalar ROM. The American Orthopaedic Foot and Ankle Society (AOFAS) Ankle–Hindfoot score was 76. Radiographs revealed healed pilon and calcaneus fractures, normal alignment of tibiotalar and subtalar joints, with some arthritic changes present to tibiotalar and subtalar joints. In conclusion, utilization of a “below the ankle” frame for the calcaneus fracture and a standard two-ring frame for the pilon fracture helps to avoid soft tissue complications and preserves tibiotalar ROM. HOW TO CITE THIS ARTICLE: Dimitroulias A, Harbacheuski R. Ipsilateral Pilon and Calcaneus Fractures: Treatment with Circular Frame without Spanning Ankle Joint. Strategies Trauma Limb Reconstr 2019;14(2):111–114.